Odpowiedzi

2010-03-08T21:18:55+01:00
A)2a+3-a+6+7a dla a=-2
2a+3-a+6+7a=8a+9=8*(-2)+9=-7
B)2z+t-3z +4t -1 dla z=5 i t=0,1
2z+t-3z +4t -1=-z+5t-1=-5+5*0,1-1=-5,5
C)13x-2y+7 -9x +y-4+x-3 dla x=0,2 y= -1
13x-2y+7 -9x +y-4+x-3=5x-y=5*0,2-(-1)=2
D) n²+n -7 +3n² -n -9-n +16 dla n= - 1/2
n²+n -7 +3n² -n -9-n +16=4n²-n=4*(-1/2)²-(-1/2)=1½
2010-03-08T21:26:35+01:00
A)2a+3-a+6+7a dla a=-2

8a+9=
-16+9=
-7

b)2z+t-3z +4t -1 dla z+5 i t+0,1

-z+5t-1=
-5+0,5-1=
-5,5

C)13x-2y+7 -9x +y-4+x-3 dla x+0,2 y+ -1

5x-y=
1+1=
2


d) n do kawadratu +n -7 +3n do kwadratu -n -9-n +16 dla n+ - 1/2

4n[2]-n=
[4*(-1/2)*-1/2)]-(-1/2)]=
[4*0,25]+1/2=
1+1/2=
1,5

99%, że dobrze i staraj się pisać "=" zamiast "+" ;p